Secrets and knowledge management strategy: the role of secrecy appropriation mechanisms in realizing value from firm innovations. Issue 2 (11th March 2019) - Hannah, David; Parent, Michael; Pitt, Leyland; Berthon, Pierre
Abstract : Purpose: The purpose of this paper is to explore in depth the mechanisms that organizations use to keep their innovations secret. This paper examines how, when and why secrecy appropriation mechanisms (SAMs) can enable innovators to appropriate value from their innovations. Design/methodology/approach: Building from an extensive literature review of innovation and secrecy, the paper presents a number of implications for theory and research in the form of testable propositions. Findings: This conceptualization proposes that SAMs can have both positive and negative effects on a number of organizational dynamics. SAMs involve tradeoffs, and the key to understanding whether they create value to organizations lies in understanding that these tradeoffs exist and the nature of these tradeoffs. Practical implications: While most managers recognize the importance of secrecy in innovations, many struggle with the practical challenges of doing so. The paper presents guidance for managers to overcome these challenges. Originality/value: This paper adds to previous research that has identified secrecy as an important appropriation mechanism for firms by digging deeper into the details of SAMs and exploring their sources, characteristics and effects.